Reconciling Post-Positivist and Post-Modern Worldviews in Climate Research and Services - Ponce de Leon, Inez Z (Archīum Ateneo, 2012)
Climate change has evolved into an almost all-encompassing issue of this generation. What had begun in the realm of the physical sciences has now proved more complex than initially anticipated, and to be inherently tied to human lifestyles and decision-making. Thus, a holistic approach to climate science requires rigorous interdisciplinary and trans-disciplinary research and practice toward implementing responsive actions on the ground. Post-modernism has emerged in the last few years as a potential interdisciplinary research paradigm for issues such as climate change because of its inclusiveness. However, it has been criticized by researchers in general because of its apparent relativism, as well as its lack of concrete metrics for evaluating the validity of findings. Scientists still mainly appeal to the traditional post-positivist approach in which there is one “truth” that is objective and can be known through careful experimentation. Post-positivism holds scientific knowledge and reputation in high regard, while often dismissing the views of non-scientists as being uninformed or lacking in depth of technical understanding.However, the complexity of the climate change issue cannot be contested; and the diversity of stakeholder voices make an already complex issue more challenging to comprehend, much less address. A variety of terms such as “resilience,” “risk,” “safety,” and “vulnerability” are used with no clear consensus about what these terms mean. Because these terms are tied to societal values, different contexts result in different meanings and, hence, implications for adaptation goals.These issues become all the more crucial given the current initiatives toward conceptualizing, developing, and implementing frameworks and infrastructures for the delivery of climate services, that is climate information tailored for the use of stakeholders in vulnerability, impact and adaptation assessments, and subsequent decision-making on policies and interventions. Our understanding of the climate problem drives our definition of goals, our formulation and implementation of sound policies, and our articulation and measurement of progress indicators. The diversity of stakeholders means a potential diversity in the understanding of what needs to be done in face of climate change and in de ning the indicators to monitor the actual progress and success of implementation. How then, do we move forward given the limitations in both current post-positivistic and post-modern approaches, and the dif culty in reconciling the two? Can we integrate the strengths of these worldviews in order to conduct rigorous research toward delivering relevant and effective services? Can the discourse be broadened to introduce both philosophical and sociological perspectives in order to navigating the nexus between science and society? We argue herein for a reconciliation, which we hope will contribute to building the foundations of interdisciplinary and transdisciplinary methodologies in climate change research and response.